PMO-141 Flagellin-induced IL-6 production is selectively impaired in patients with cirrhosis. (28th May 2012) - Alazawi, W; Spyrou, A; Lahiri, R; Waters, J; Foster, G R
Abstract : Introduction: The innate immune response is an important determinant of progression in chronic inflammatory liver diseases such as alcoholic (ALD) and non-alcoholic fatty liver disease (NAFLD). Sepsis is a frequent cause of hepatic decompensation and some authors suggest a role for toll-like receptor (TLR) sensing of gut-derived pathogens (motile and gram-negative organisms) in disease progression. Paresis of the innate immune system has been described in patients with decompensated liver disease, but the function of TLRs in compensated disease has received scant attention. Our aim was to assess TLR responsiveness in patients with compensated ALD and NAFLD using a combinatorial experimental design, measuring LPS- and flagellin-induced TNFα and IL-6 production. Methods: Consenting adult outpatients with compensated ALD or NAFLD were recruited. Diagnoses were confirmed by casenote review. Exclusion criteria included alternative aetiologies, decompensated disease, other systemic immune-related illnesses, and immunosuppression (including steroids). Normal healthy volunteers without liver disease were also recruited. Monocytes isolated from peripheral blood mononuclear cells were stimulated with low dose LPS and flagellin. The production of TNF-α and IL-6 was assayed in supernatants and in patient sera by ELISA. Results: We included 28 patients and six normal controls. Patients with compensated cirrhosis have a selective defect in flagellin-induced IL-6 production (330±117 pg/ml) compared to patients with non-cirrhotic ALD or NAFLD (896±146 pg/ml; p=0.01) or healthy controls (764±96 pg/ml). There were no differences in flagellin-induced TNFα nor in LPS-induced cytokine production. There were no differences between the three groups in serum concentrations of TNF, IL-6 and RANTES. Conclusion: Paresis of the innate immune response is not universal; there is selective impairment of TLR5-mediated IL-6 production in patients with compensated cirrhosis compared to non-cirrhotic patients. These data identify potential signalling pathways that may be involved in the progression of liver disease or in the susceptibility of patients with cirrhosis to bacterial infections. Competing interests: None declared.